Sistem Aplikasi Absensi Guru Menggunakan Qr Code Berbasis Android Pada Smp Negeri 1 Karang Bahagia Kabupaten Bekasi - Mulyadi, Rudi; Rahardjo, Sugeng Budi; Sasongko, Ananto Tri (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The attendance system is used to obtain records regarding attendance. In a particular agency in the field of education, the presence of the teacher is one of the main factors that is very important in evaluating its performance. However, at SMP Negeri 1 Karang Bahagia, the level of teacher absence violations is quite high so that it can easily manipulate attendance data, as well as data collection for a teacher who does not enter with the excuse of illness, permit, or leave, which is less effective and efficient and quite difficult in monthly attendance data recapitulation due to easy loss due to forgetting to save, damage by water or fire, and others. This study aims to design and build an attendance system that will make it easier for teachers to carry out the attendance process and for Administrative administrators to recapitulate attendance data. In developing this system, the author uses the waterfall method. This attendance system is automatically designed using the Quick Response Code (QR Code) to scan the attendance QR, as well as adding automatic features to the face photo taking section as proof of attendance and giving a location point when making an absence. This system has been completed and tested. according to the scenario that has been designed. After testing the attendance system, it runs well, makes it easier to collect absentee data by the teacher in controlling daily attendance, and makes it easier to recapitulate monthly reports so that it is more effective and efficient.